Exploring the leads from nature to heal helminthiasis - NEETU DESHWAL (International Journal of Pharma and Bio Sciences, 2019)
The escalating pervasiveness of anthelmintic resistant strains of helminths, drug residues in animal products and high cost of conventional anthelmintics has created an interest in studying medicinal plants as an alternative source of anthelmintics. The plant Aegle marmelos and Allium sativum have great medicinal value and used for the treatment of inflammation, asthma, hypoglycaemia, febrifuge, hepatitis and management of blood pressure, atherosclerosis, high cholesterol, heart attack, coronary heart disease A significant anthelmintic effects were observed on live adult Pheretima posthuma worms in terms of the paralysis and death of the worms at different concentratio ns The Anthelmintic activities of petroleum ether extract of leaves of Aegle marmelos and n-hexane extracts of bulb of Allium sativum were evaluated separately on Indian earthworm Pheretima posthuma in comparison to reference standard Albendazole. A significant anthelmintic effects were observed on live adult Pheretima posthuma worms in terms of the paralysis and death of the worms at different concentrations. Data revealed that extracts of both plants showed anthelmintic activity i.e paralysis and death of earthworm at different concentrations. The activities are well comparable with the standard drug, Albendazole as positive control.